A Novel Kinetic Spectrophotometric Method for the Determination of Dopamine in Biological and Pharmaceutical Samples - M. Reza Shishehbore; Adel Asgharpoor; N. Nasirizadeh (Journal of Chemistry)
A sensitive and accurate method for quantitative determination of dopamine was introduced. The proposed method is based on inhibitory effect of dopamine on the oxidation of thionine by bromate in acidic media. The change in absorbance was followed spectrophotometrically at 601 nm. The dependence of sensitivity on the reaction variables was investigated and optimized to obtain the maximum sensitivity. Under optimum experimental conditions, calibration curve was linear over the range 0.2–103.3 μg mL−1 of dopamine. The relative standard deviations () of 0.5, 1.0, 5.0, and 30.0 μg mL−1 of dopamine were 1.13, 1.02, 0.99, and 0.97%, respectively. The limit of detection was 0.057 μg mL−1 of dopamine. The effect of diverse species was also investigated. The developed method was successfully applied for the determination of dopamine in pharmaceutical and biological samples.